Changes in cerebral blood flow in rheumatology patients treated with rituximab - Utku, Uygar; Çetin, Gözde; Atilla, Nurhan (The European Research Journal, 2018)
Objective: We aimed to assess the effects of rituximab therapy on cerebral hemodynamics in rheumatic patients with transcranial Doppler (TCD) ultrasonography. Methods: The study included seven patients aged 20-65 years (2 patients with secondary interstitial lung involvement to rheumatoid arthritis, 3 patients with systemic lupus erythematosus and lupus nephritis, 2 patients with scleroderma and secondary interstitial lung disease) who received rituximab treatment due to rheumatic diseases. Healthy control group (non-rheumatic group) consisted of seven age and sex-matched, randomly selected persons did not have risk factors for atherosclerosis. Bilateral middle cerebral artery peak-systolic, end-diastolic, and mean blood flow velocities, Gosling’s pulsatility index values, and Pourcelot’s resistance index values were recorded with TCD by a neurosonologist before rituximab administration. Control TCD performed to the rheumatic group after six months from the last rituximab dosage. Results: One patient was male and six patients were female. Peak-systolic, end-diastolic and mean blood flow velocities of rheumatic patients were significantly higher than healthy group (p < 0.001). Peak-systolic, end-diastolic and mean blood flow velocities of rheumatic patients were significantly decreased after rituximab therapy (p < 0.001). Conclusions: This study highlights that the increased cerebral blood flow is indirectly associated with atherosclerosis regarding persistent inflammation in patients with rheumatic diseases. It was thought that treatment with rituximab could reverse this situation.